Tracing fungi secondary metabolites in Brazil nuts using LC-MS/MS - Silva, Otniel Freitas (2011)
This screening aimed to evaluate quantitatively the occurrence of fungal metabolites in Brazil nuts. Nuts were collected from Agroforest production areas in Amazon basin region. A total of 235 mycotoxins (including the most prominent ones) was screened by a multi-mycotoxin method based on HPLC-MS/MS. The recovery of metabolites by the method was between 56 and 136%. Fifteen mycotoxins were detected and quantified, in at least one sample; namely, aflatoxins (AFB1, AFB2, AFG1, and AFM1), sterigmatocystin, methyl-sterigmatocystin, kojic acid, citrinin, cyclosporin A, cyclosporin C, cyclosporin D, cyclosporin H, rugulosin, alternariol-methylether and emodin. This is the first study dealing with the detection of the latter nine metabolites in Brazil nuts. Alternariol-methylether (from 0.75 to 3.2 μg/kg) was the only metabolite detected in all analyzed samples.